Company‐sponsored egg freezing: an offer you can't refuse?. (21st October 2021) - Petersen, Thomas Søbirk; Hansen, Rune
Abstract: The aim of this article is to argue that one of the central arguments against company‐sponsored non‐medical egg freezing, namely that this practice is contrary to the reproductive autonomy of women, can be difficult to sustain under certain conditions. More specifically, we argue that company‐sponsored egg freezing is not necessarily in conflict with the most common requirements for autonomous choice. That is, there is no reason to assume that employees cannot be adequately informed beforehand about what is scientifically known about the practice, and/or that they lack the required capacity to understand and process this information. Although they may feel a certain pressure to comply with the wishes of their employer, this concern can plausibly be alleviated through privacy regulations. In any event, such pressure is arguably not stronger than or relevantly different from other types of pressure on the labour market that most people readily accept as being ethically acceptable. Finally, we argue that company‐sponsored non‐medical egg freezing may mitigate certain types of oppressive socialization, although it may well perpetuate others, and should in any case arguably be dealt with through guidelines and counselling, which would ensure that women make autonomous choices when companies offer egg freezing.